Inovasi Kawal Ketat Status Gizi Kelompok Rentan Sebagai Upaya Mengatasi Stunting di Puskesmas Kurai Taji Pariaman Selatan - Herza Netti; Aldri Frinaldi; Sri Hidayati (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
Stunting in Indonesia is a significant figure. Based on data from the 2019 Indonesian Youth Nutrition Survey (SSGBI), the prevalence of stunting in Indonesia is 27.7%, which is still relatively high compared to the WHO threshold of 20%. To overcome these problems, the government has developed a National Action Plan for Nutrition and Food Security through the National Anti-Obesity Movement and is currently taking various steps. However, this does not help reduce stunts in accordance with the goals given. So we need fresh ideas in the form of innovative sticky rice wire (Strict Control of the Nutritional Status of Vulnerable Groups). The purpose of this innovation was made as a step to accelerate the reduction of stunting rates in the city of Pariaman. The method used in this study uses descriptive methods using literature studies. According to Sugiyono descriptive research method is a method used to describe or analyze a research result but not used to make broad conclusions. From the policies that have been made, it can be concluded that the city of Pariaman has experienced a decline in the stunting rate from 11.2% to 9.1% in September 2022 and the hope of the Pariaman city government at the end of 2022 the stunting rate can be 5%.